Preventing postnatal transmission of HIV-1 through breast-feeding: modifying infant feeding practices. - (:unkn) unknown (My University, 2004)
Approaches to reducing or preventing the risk of postnatal transmission through breast-feeding include the avoidance of all breast-feeding and the use of exclusive replacement feeds or exclusive breast-feeding for a limited duration with early and rapid cessation of breast-feeding around 4-6 months of age. The efficacy and safety of the latter approach have not been established and studies are in progress to provide further information. In addition, inactivation of HIV in breast milk would allow breast-feeding to continue while reducing the risk of postnatal transmission of HIV and may be usefully applied in certain circumstances, such as for premature infants or while a mother recovers from mastitis. In this review, experience is reported from clinical trials or studies additional to their main objective of assessing rates and risk factors for mother-to-child transmission. This may inform policy, programming, and training options and may be especially valuable in the absence of conclusive data on the efficacy of the interventions to be applied during the breast-feeding period.
Keywords: African Research